Will the increase of medical equipment affect medical expenditure? Empirical evidence from a quasi-experiment in China - Qiwei Deng; Zhongliang Zhou; Chi Shen; Dan Cao; Dantong Zhao; Yaxin Zhao; Jianmin Gao (BMC Health Services Research)
Abstract Background Many studies have shown that using new technologies and medical equipment contributes to increasing health expenditure. Relatively less empirical studies have measured the impact of medical equipment on rising medical costs in China. Against this backdrop, we aim to examine whether the large-scale medical equipment deployment explains the increase in health expenditure. Methods Quasi-experimental research design with a difference-in-differences approach was adopted to explore whether an increase in the number of large-scale medical equipment impacts on outpatient and inpatient costs. Data were obtained from the 2011–2017 Health Financial Annals in Shaanxi province, China. Results The increase in the number of large-scale medical equipment by 1 — regardless of the initial configuration — resulted in the increase of the average cost per outpatient visit and the average cost per inpatient visit by 10.6% (p < 0.05) and 8.0% (p < 0.05), respectively. Our complex difference in differences model illustrates that the increase in the number of large-scale medical equipment by 1 — regardless of the initial configuration—results in an increase in the average diagnostic cost per outpatient visit and the average diagnostic cost per inpatient visit by 27. 3% (p < 0.01) and 25. 5% (p < 0.01), respectively. Conclusions Our findings show that the medical expenditure differs significantly with the increase in the number of large-scale medical equipment. This study mainly revealed the relationship between the growth of the number of large-scale medical equipment and medical expenditure. Our novel perspective was used to measure the phenomenon of excessive use, and to explain the social phenomenon of inaccessible and expensive medical care in China.